Physiological variations in hypovirus-infected wild and model long-term laboratory strains of Cryphonectria parasitica - Popović, Maja; Nuskern, Lucija; Peranić, Karla; Vuković, Rosemary; Katanić, Zorana; Krstin, Ljiljana; Ćurković-Perica, Mirna; Leigh, Deborah Marie; Poljak, Igor; Idžojtić, Marilena; Rigling, Daniel; Ježić, Marin (Frontiers in Microbiology, 2023)
Forest ecosystems are highly threatened by the simultaneous effects of climate change and invasive pathogens. Chestnut blight, caused by the invasive phytopathogenic fungus Cryphonectria parasitica, has caused severe damage to European chestnut groves and catastrophic dieback of American chestnut in North America. Within Europe, the impacts of the fungus are widely mitigated through biological control that utilises the RNA mycovirus: Cryphonectria hypovirus 1 (CHV1). Viral infections, similarly to abiotic factors, can cause oxidative stress in their hosts leading to physiological attrition through stimulating ROS (reactive oxygen species) and NOx production. To fully understand the interactions leading to the biocontrol of chestnut blight, it is vital to determine oxidative stress damage arising during CHV1 infection, especially considering that other abiotic factors, like long-term cultivation of model fungal strains, can also impact oxidative stress. Our study compared CHV1-infected C. parasitica isolates from two Croatian wild populations with CHV1-infected model strains (EP713, Euro 7 and CR23) that have experienced long-term laboratory cultivation. We determined the level of oxidative stress in the samples by measuring stress enzymes’ activity and oxidative stress biomarkers. Furthermore, for the wild populations, we studied the activity of fungal laccases, expression of the laccase gene lac1, and a possible effect of CHV1 intra-host diversity on the observed biochemical responses. Relative to the wild isolates, the long-term model strains had lower enzymatic activities of superoxide dismutase (SOD) and glutathione S-transferase (GST), and higher content of malondialdehyde (MDA) and total non-protein thiols. This indicated generally higher oxidative stress, likely arising from their decades-long history of sub-culturing and freeze-thaw cycles. When comparing the two wild populations, differences between them in stress resilience and levels of oxidative stress were also observed, as evident from the lower MDA content. The intra-host genetic diversity of the CHV1 had no discernible effect on the stress levels of the virus-infected fungal cultures. Our research indicated that an important determinant modulating both lac1 expression and laccase enzyme activity is intrinsic to the fungus itself, possibly related to the vc type of the fungus, i.e. vegetative incompatibility loci.